Correlation between electrophoretic types B1 and B2 of carboxylesterase B and host-dependent factors in Escherichia coli septicaemia. - Picard, B. (Cambridge University Press, 1988)
Electrophoretic types B1 and B2 of carboxylesterase B produced by strains of Escherichia coli isolated from 100 septicaemia cases were correlated with alpha-haemolysin and mannose resistant haemagglutinin (MRHA) production and with clinical data including eventual underlying diseases, origin of septicaemia and evolution. Electrophoretic type B2 was phenotypically linked with alpha-haemolysin and MRHA production. The proportion of type B2 isolates varied significantly with occurrence of an underlying illness (45% for patients without an underlying disease and 22% for compromised patients) and with the site of origin of the septicaemia (40% for those of urinary origin and 18% for infection of digestive origin). In the former infections, type B2 isolates were obtained in the majority from male patients while type B1 isolates predominated in women. The septicaemias associated with type B1 were characterized by a lower proportion of isolates producing alpha-haemolysin and MRHA and by a greater frequency of septic shock and death than those associated with type B2. These facts emphasize the importance of host-dependent factors in E. coli septicaemia.